Methylation-Spanning Linker Libraries Link Gene-Rich Regions and Identify Epigenetic Boundaries in Zea mays - Yuan, Yinan; SanMiguel, Phillip J.; Bennetzen, Jeffrey L. (Genome Research, 2002)
Complex cereal genomes are largely composed of small gene-rich regions intermixed with 5 kb to 200 kb blocks of repetitive DNA. The repetitive DNA blocks are usually 5-methylated at 5′-CG-3′ and 5′-CNG-3′ cytosines in most or all adult tissues, while the genes are generally unmethylated at these sites. We have developed methylation-spanning linker library (MSLL) technology as a tool to span large methylated DNA blocks and thereby link unmethylated genic regions. MSLL clones contain insertions of large fragments that are size fractionated over gels after complete digestion of total genomic DNA with restriction enzymes that are sensitive to the 5-methylation of cytosines in 5′-CG-3′ and 5′-CNG-3′ sequences. Our data indicate that the end sequences of maize MSLL clones are greatly depleted in repetitive DNAs and enriched in genes relative to total genomic DNA. Combined with other gene-enrichment approaches, MSLL technology can efficiently generate fully-linked contiguous sequences in complex genomes that are resistant to shotgun sequencing.